Nilai Moral Jawara Banten Dalam Pendidikan Karakter Siswa - Nur Hidayat; Achmad Hufad; Suroso Mukti Leksono (Peneliti.net, 2022)
Jawara of a special position in Banten society. Jawara was part of the subculture in Banten society that has a special position other than